Plasma single-stranded DNA autoantibodies in the diagnosis of Hirschsprung’s disease - Wang, Bingtong; Yao, Yongxuan; Fang, Wenlin; Liu, Yanqing; Zhong, Wei; He, Ye; Lai, Yulu; He, Qiuming; Zhu, Yun; Lan, Chaoting (Frontiers in Medicine, 2022)
Background Hirschsprung’s disease (HSCR) is a neonatal enteric nervous system (ENS) disease characterized by congenital enteric ganglion cell loss. The only treatment is aganglionic bowel segment resection and innervated bowel segment reconstruction. Delayed diagnosis and treatment cause postoperative complications such as intractable constipation and enterocolitis. Existing preoperative HSCR diagnostic methods have shortcomings such as false positives, radiation and invasiveness. Methods We used the robust linear model (RLM) for normalization and the M statistic for screening plasma human autoimmune antigen microarrays and quantitatively assessed single-stranded DNA (ssDNA) antibody levels with enzyme-linked immunosorbent assay (ELISA). Results The autoimmune antigen microarray revealed that autoantibodies were higher in HSCR plasma than in disease control (DC) and healthy control (HC) plasma. ssDNA antibodies in HSCR plasma were significantly higher than those in DC and HC plasma. Quantitative ssDNA antibody level detection in plasma by ELISA showed that HSCR (n = 32) was 1.3- and 1.7-fold higher than DC (n = 14) and HC (n = 25), respectively. ssDNA antibodies distinguished HSCR from non-HSCR (HC and DC), achieving an area under the curve (AUC) of 0.917 (95% CI, 0.8550–0.9784), with a sensitivity of 96.99% and a specificity of 74.63%. Conclusion ssDNA antibodies in plasma can serve as a diagnostic biomarker for HSCR in the clinic.